Is knowledge and practice of oral rehydration therapy suboptimal? Assessment at Federal Medical Center, Asaba, South-South Nigeria - Ezeonwu, Bertilla U.; Ayodele, Ayodeji; Ajaegbu, Obinna C.; Mbagwu, Nkemjika E.; Ovemeso, Odiri; Okolo, Angela A. (International Journal Of Community Medicine And Public Health, 2017)
Background: Oral rehydration therapy (ORT) is a core component of the childhood survival strategies to reduce child mortality and morbidity due to diarrhoeal disease with its fatal dehydrating complication of acute kidney injury. This strategy is indispensable to the attainment of the International Society of Nephrology’s (ISN) aim to eliminate preventable deaths from acute kidney injury (AKI) by year 2025. Diarrheal disease is the second most common cause of morbidity and mortality in children at our centre. This interventional study assessed the knowledge and the practice of ORT among caregivers, educated and trained them on the management of diarrhoeal diseases and practice of ORT. Oral rehydration salt (ORS) and zinc tablets were also distributed. Methods: An interviewer-administered questionnaire was used following informed consent. Consented care givers of wards attendees of FMC Asaba were assessed on their knowledge and their practice of ORT, educated on childhood diarrheal diseases, trained on practice of ORT and had ORS and zinc tablets distributed to them. These assessments were done on the spot and 6 weeks after the health talk, from July 2015 to December 2015. Results: There were 266 respondents and 231 were mothers. The immediate impact of the health talk on the knowledge and the practice of ORT was laudable, p≤0.0001 and educational attainment of the respondent influenced the immediate post health talk knowledge of ORT, p=0.009. The age of the respondent predicted the long term impact of health talk on practice of ORT, p=0.020. Conclusions: Knowledge and practice of ORT are not optimal but can be improved by regular education.